SEMANTIC-METHODICAL CHARACTERISTICS OF INTEGRAL FRAGMENTS (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The article describes the unique semantic and stylistic aspects of the Uzbek language in fiction. It examines the semantic and methodological features of linguistics.